2016
DOI: 10.18280/ijht.34s241
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electrochromic Windows for Residential Applications

Abstract: Electrochromic windows can play an important role for energy saving as well as for controlling the visual and thermal conditions inside a room. This paper starts with a critical review and the state-of-art regarding the products today commercially available as well as the studies conducted on full scale electrochromic windows. The analysis allows to define the main parameters characterizing the electrochromic windows with particular regard to their optical, thermal and electrical characteristics, while assumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…The application range of such windows is wide. Patient examination rooms, business meeting rooms, glassing of cars, planes, modern buildings, displays for currency, prices, temperature -is a far from complete list of applications for such devices [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The application range of such windows is wide. Patient examination rooms, business meeting rooms, glassing of cars, planes, modern buildings, displays for currency, prices, temperature -is a far from complete list of applications for such devices [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A complete review of existing and commercially available EC glazing was presented by Sibilio et al [44], in 2016. They reported that EC layers are typically coupled with double or triple glazing, including a low-E coated glass pane, to maximize thermal performance.…”
Section: Of 17mentioning
confidence: 99%
“…EC devices can allow an energy savings of up to 59% [44], but the actual benefits are often unrelated to the technology itself. Orientation, climatic conditions, latitude location and control strategy dramatically affect the performance of a smart window.…”
Section: The Role Of Control Strategiesmentioning
confidence: 99%
“…In order to allow for experimental studies to assess the in-situ visual performances of fullscale smart windows, an experimental station was designed and set-up at the Department of Engineering of the University of Sannio (Ascione et al, 2016;Sibilio et al, 2016). The station consists of a steel structure placed on a turntable, with external size of 6.00 m x 6.00 m and height of 5.50 m. The facility is equipped with a double-hang wood frame window with a total size of 2.000 m x 1.200 m, a ratio between glass area and total window area equal to 0.59; each hang has a glazing with size of 0.785 m x 0.900 m. In this paper, the first results of the in-situ visual characterization of the two full-scale double ED glazings, manufactured by Gesimat (GESIMAT), were presented.…”
Section: Test Facility and Measurements Set Upmentioning
confidence: 99%